2017
DOI: 10.1152/ajpgi.00149.2016
|View full text |Cite
|
Sign up to set email alerts
|

The influence of rosuvastatin on the gastrointestinal microbiota and host gene expression profiles

Abstract: Statins are the most widely prescribed medications worldwide for the treatment of hypercholesterolemia. They inhibit the activity of 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-R), an enzyme involved in cholesterol synthesis in higher organisms and in isoprenoid biosynthesis in some bacteria. We hypothesized that statins may influence the microbial community in the gut through either direct inhibition or indirect mechanisms involving alterations to host responses. We therefore examined the impact of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 63 publications
1
37
1
2
Order By: Relevance
“…The interactions between statins and bile acids, which share transporters in the intestine, may underlie the interplay between statins and gut microbial composition. Recently, Nolan et al showed in a murine model that Rosuvastatin affected bile acid metabolism and impacted the expression of inflammatory markers known to influence microbial community structure in the gut (i.e., RegIIIy and Camp) . In addition, other side effects of statins such as constipation or laxative effects could potentially arise from gut microbiota alteration.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between statins and bile acids, which share transporters in the intestine, may underlie the interplay between statins and gut microbial composition. Recently, Nolan et al showed in a murine model that Rosuvastatin affected bile acid metabolism and impacted the expression of inflammatory markers known to influence microbial community structure in the gut (i.e., RegIIIy and Camp) . In addition, other side effects of statins such as constipation or laxative effects could potentially arise from gut microbiota alteration.…”
Section: Discussionmentioning
confidence: 99%
“…The first statin, "Mevastatin," which is a metabolic product of Penicillium citrinum, was initially characterized for its antibiotic properties, and statins are now considered as adjuvant antibiotics that can impact antimicrobial resistance (Ko et al, 2017). Consequently, the role of statins deserves to be explored beyond their traditionally established indications in light of their antimicrobial potential as a regulator of gastrointestinal microbiota (Nolan et al, 2017). Only a few studies have shown the impact of the microbiota on statin efficacy.…”
Section: Impact Of the Microbiota On Hypocholesterolemic Drug Efficacymentioning
confidence: 99%
“…term exposures [17]. Statins, the most effective lipid-lowering drugs, which are widely used for the treatment of hypercholesterolemia owing to their inhibition of HMGR protein [36], also have off-target effects including anti-inflammation function [37,38].…”
Section: Plos Onementioning
confidence: 99%
“…In addition, although the research on the antibacterial activity of FLU has been scarce and more studies are needed [58], it seems that its antifungal activity may be higher than that of other statins [59]. In another study, administration of ROS to mice randomly in the diet for 28 days significantly influenced the structure of the gut microbiota [17]. Some researchers found that ATO and SIM may have a more potent antibacterial activity than ROS, but the clinical strains were less sensitive to statin compared with the standard bacteria [60].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation